Audit of The Effective Use of the Braden Scale - Cadman, Rosa (2011)
Aim The aim of this audit was to establish the level of Braden Pressure Ulcer Risk Assessment Tool (BPURAT) documentation by nursing staff on the adult in-patient population with stage 3 or 4 pressure ulcers (PU) present in an East Midlands Hospital Trust. The recommendations from the Nottingham University Hospital’s essence of care benchmarks (2010) and the National Institute for Clinical Excellence (NICE) pressure ulcer guidelines (2005) were used to assess compliance.